Chemometric approach to validating faecal sterols as source tracer for faecal contamination in water. - Saim, Norashikin; Osman, Rozita; Abg Spian, Dayang Ratena Sari; Jaafar, Mohd Zuli; Juahir, Hafizan; Abdullah, Md Pauzi; Ab Ghani, Fuzziawati (Elsevier, 2009)
Faecal sterols detection is a promising method for identifying sources of faecal pollution. In this study, faecal contamination in water samples from point source (sewage treatment plants, chicken farms, quail farms and horse stables) was extracted using the solid phase extraction (SPE) technique. Faecal sterols (coprostanol, cholesterol, stigmasterol, β-sitosterol and stigmastanol) were selected as parameters to differentiate the source of faecal pollution. The results indicated that coprostanol, cholesterol and β-sitosterol were the most significant parameters that can be used as source tracers for faecal contamination. Chemometric techniques, such as cluster analysis, principal component analysis and discriminant analysis were applied to the data set on faecal contamination in water from various pollution sources in order to validate the faecal sterols’ profiles. Cluster analysis generated three clusters: coprostanol was in cluster 1, cholesterol and β-sitosterol formed cluster 2, while cluster 3 contained stigmasterol and stigmastanol. Discriminant analysis suggested that coprostanol, cholesterol and β-sitosterol were the most significant parameters to discriminate between the faecal pollution source. The use of chemometric techniques provides useful and promising indicators in tracing the source of faecal contamination.